Operational criteria for the design of front-office processes in multi-channel service delivery systems - Sousa, Rui (2013)
This paper identifies relevant operational factors that affect the design of front-office processes in Multi-Channel Service Delivery Systems. Based on two in-depth case studies in banking and telecommunications, we distinguish four operational factors: i) characteristics of the inputs and outputs of the service activities; ii) characteristics of the transformation taking place; iii) the expected utilization; iv) the economics of developing the activities in the channels. Building on these results, we propose a stepwise approach for addressing the design of front-office models for MC services.